Some Features Of Sensorineural Hearing Loss In Neurological Practice (Texas Journal of Medical Science, 2025)
This study presents scientific results on certain aspects of sensorineural hearing loss in neurological practice. Modern research indicates that sensorineural hearing loss is associated with oxidative stress, microcirculation disorders, and inflammatory processes. The introduction of new diagnostic methods, such as molecular genetics, neurodegeneration biomarkers, and imaging techniques, has improved early diagnosis and disease prognosis. Thus, for the treatment of sensorineural hearing loss occurring in neurological diseases, modern therapeutic strategies include the use of neuroprotectors, antioxidants, gene therapy, and cellular regeneration of the auditory nerve